Some Preliminary Investigations on the Rainfall Interception by Leaf Litter - Dabral, B. G., Premnath, Ramswarup (Indian Forester, 1963)
An attempt has been made to study the interception caused by litter in four forest species. It has been observed that sal and teak litter induced greater interception than done by chir, pine and bamboo species. It was also observed that interception values were higher with lower amounts and intensities of rainfall. The amount of litter present also influenced the interception values.